Observations of multi-microsecond VHF pulsetrains in energetic intracloud lightning discharges - A. R. Jacobson; R. H. Holzworth; X.-M. Shao (Annales Geophysicae, 2011)
Certain intracloud lightning discharges emit energetic, multi-microsecond pulsetrains of radio noise. Observations of this distinctive form of lightning date from 1980 and have involved both ground-based and satellite-based radio recording systems. The underlying intracloud lightning discharges have been referred to as "Narrow Bipolar Pulses", "Narrow Bipolar Events", and "Compact Intracloud Discharges". An important discriminant for this species of radio emission is that, in the range above ~30 MHz, it consists of several microseconds of intense radio noise.